Duration and ice thickness of a Late Holocene outlet glacier advance near Narsarsuaq, southern Greenland - Puleo, Peter J. K.; Axford, Yarrow (Climate of the Past, 2023)
Greenland Ice Sheet (GrIS) outlet glaciers are currently losing mass, leading to sea level rise. Reconstructions of past outlet glacier behavior through the Holocene help us better understand how they respond to climate change. Kiattuut Sermiat, a southern Greenland outlet glacier near Narsarsuaq, is known to have experienced an unusually large Late Holocene advance that culminated at ∼1600 cal yr BP and exceeded the glacier's Little Ice Age extent. We report sedimentary records from two lakes at slightly different elevations in an upland valley adjacent to Kiattuut Sermiat. These reveal when the outlet glacier's surface elevation was higher than during the Little Ice Age and constrain the associated outlet glacier surface elevation. We use bulk sediment geochemistry, magnetic susceptibility, color, texture, and the presence of aquatic plant macrofossils to distinguish between till, glaciolacustrine sediments, and organic lake sediments. Our 14C results above basal till recording regional deglaciation skew slightly old due to a reservoir effect but are generally consistent with regional deglaciation occurring ∼ 11 000 cal yr BP. Neoglacial advance of Kiattuut Sermiat is recorded by deposition of glaciolacustrine sediments in the lower-elevation lake, which we infer was subsumed by an ice-dammed lake that formed along the glacier's margin just after ∼ 3900 cal yr BP. This timing is consistent with several other glacial records in Greenland showing neoglacial cooling driving advance between ∼ 4500–3000 cal yr BP. Given that glaciolacustrine sediments were deposited only in the lower-elevation lake, combined with glacial geomorphological evidence in the valley containing these lakes, we estimate the former ice margin's elevation to have been ∼ 670 m a.s.l., compared with ∼ 420 m a.s.l. today. The ice-dammed lake persisted until the glacier surface fell below this elevation at ∼ 1600 cal yr BP. The retreat timing contrasts with overall evidence for cooling and glacier advance in the region at that time, so we infer that Kiattuut Sermiat's retreat may have resulted from reduced snowfall amounts and/or local glaciological complexity. High sensitivity to precipitation changes could also explain the relatively limited Little Ice Age advance of Kiattuut Sermiat compared with the earlier neoglacial advance.
Publisher: Copernicus GmbH